SIKAP MAHASISWA JURUSAN KK FT UNP TERHADAP PENGGUNAAN PENYEDAP RASA DAN PEWARNA SINTETIS DALAM PENGOLAHAN MAKANAN - Angrayny, Ayu; Yulastri, Asmar; Fridayati, Lucy (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2012)
This research aimed to describe student attitude of flavoring and synthetic dyes in food processing. Including cognitive, affective, and conative indicators. The The population in this research is the attitude of family welfare major of technic department of UNP 2008 untill 2010 who have been had food material science in the first class which are 163 persons. The sampling technic is propotionate random sampling with 48 samples. For synthetic flavor 49% respondents have the good attitude, 60,4% for cognitive indicator, 60,4% for affective and 65.1% for conative of the use of synthetic flavor in food processing. For synthetic dyes 60.4% respondents have the good attitude, 60.4% for cognitiveindivator, 67.4% for affective and 65.1% for conitive of the use of synthetic dyes. The result of score T analysis shows that the students have the negtive attitude of flavoring and synthetic dyes use. Negative means that the students not use the flavor and synthetic dyes in food processing.